Mechanical Properties of Gas Storage Sandstone under Uniaxial Cyclic Loading and Unloading Condition - Zhao, Baoyun; Wu, Yingjie; Yang, Jiaosheng; Sun, Juncang; Huang, Wei; Li, Ziyun; Zhang, Shuhan (Periodica Polytechnica Civil Engineering, 2023)
In order to study the mechanical properties and damage evolution of the gas storage surrounding rock under the periodic injection-production process, the uniaxial cyclic loading and unloading tests of sandstone were carried out by TFD-2000 microcomputer servo-controlled rock triaxial testing machine. Results shown that the compressive strength of gas storage sandstone specimens were gradually decreases with increasing of the stress amplitude after 200 cycles. The stress-strain curve under uniaxial cyclic loading and unloading condition formed hysteresis loops, and the hysteresis loop presented sparse-dense-sparse when the stress amplitude was relative higher. The residual strains can be divided into three stages of decay deformation stage, stable deformation stage and accelerated deformation stage when the stress amplitude is 8~32 MPa, this phenomenon is very similar to the creep behavior of rocks. The energy evolution of sandstone under cyclic loading and unloading was analyzed and the damage evolution low of which was also discussed in detail, the damage variable defined by energy dissipative ratio accumulation can well reflect the damage development of sandstone under uniaxial cyclic loading and unloading. A nonlinear visco-plastic body was proposed by considering the accelerate stage of curves of the axial residual strains, and used the nonlinear visco-plastic body to replace the visco-plastic body of the traditional Nishihara model, a nonlinear viscoelastic-plastic model for cyclic loads was established and the applicability of the model is verified. The research results provide certain reference value for the construction and maintenance of gas storage.